PERANAN MUSIK DALAM IBADAH GEREJA - Linda Mutiara Lumban Tobing (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2023)
In church worship, music has a permanent place in worship and cannot be separated from worship.This is because the congregation has experienced and has the belief that humans exist in this world solely because of God's grace. There is nothing that can be done by believers except from answer this grace through thanks and praise. The presence of music can also increase the passion and atmosphere in worship. The atmosphere and passion generated by the sounds and songs that are sung are important elements that must be carried out in every service. Therefore music plays an important role in church services. Talking about music in church services, there will be a question, what is the actual role of music in church services? To answer these questions, the author uses a qualitative research method of literature study, by searching for data through journals, books, the internet, documents and Bible verses to get answers to the questions above. It is intended that the church realizes, understands and has openess to the importance of the music role in church worship. The results of this study concluded that the role of music in church worship is as a means of vertical communication to God, as a means of horizontal communication that can witness Christian faith to non-believers, music can unite and provide consolation, and as a means of church growth.